The European gas market: Emancipating from Russia - Vasily Astrov; Doris Hanzl-Weiss (The Vienna Institute for International Economic Studies (wiiw), 2025)
Despite the formal absence of sanctions, gas trade between Russia and the EU has effectively collapsed over the past three and a half years. This has been the outcome of several factors: the EU strategy of reducing dependence on Russian gas, Russia's own supply cuts, physical damage to the crucial pipeline infrastructure and Ukraine's reluctance to prolong the gas transit contract. The resulting shock of reduced Russian supplies has primarily been absorbed via energy savings, while gas imports from other countries have increased only insignificantly. The case studies of three Central European EU member states: Slovakia, Czechia and Hungary - which had all been highly dependent on Russian gas before the start of the war in Ukraine but have adopted very different diversification strategies over the past few years - suggest that the negative effects from reduced Russian supplies could be minimised through the precautionary measures taken and also because of the interconnected nature of these countries' gas networks with those of other EU countries. Of the four main pipelines that used to bring Russian gas to Europe before the war, only TurkStream remains in operation, although its future is also potentially uncertain. Against this background, European countries would be well advised to expand their gas storage capacities in order to cushion themselves from any future supply shocks and reduce dependence on short-term price fluctuations.
Keywords: Q4; 330; gas dependency; energy consumption; gas storage